O ENSINO DA FÍSICA NO CONTEXTO DA HISTÓRIA, CIÊNCIA, TECNOLOGIA E SOCIEDADE – UMA PROPOSTA PARA A APRENDIZAGEM SIGNIFICATIVA - MACEDO, ANDRÉIA HORNES (2016)
The teaching of physics, before advances that are occurring, cannot be restricted to the study of isolated phenomena, because it requires much more than ready formulas and definitions. Insert in the classroom context the historical aspects involving the development of scientific theories, transforms completely the simplistic, intuitive and linear science, which conduce to understanding the technological advances and its purpose over time, and the reaction suffered by the society and the impacts related to scientific progress. This study aims to develop a teaching strategy through an integrated approach, involving the context of History, Science, Technology and Society (HSTS) in view of a meaningful learning, in which physical concepts are relevant to students. Also it will be described a teaching sequence on the Photoelectric Effect, Modern Physics and Contemporary contents, third year of high school, with the steps of the proposal, highlighting the importance of Physical education in approach HCTS. The History of Science has an immeasurable importance in the understanding of physical concepts, its fluidity can involve science, technology and society, in a way that these aspects can be integrated significantly by the subjects of the process.